A new model for money demand in Denmark: Money demand in a negative interest rate environment - Jonas Ladegaard Hensch (Danmarks Nationalbank, 2019)
Within a cointegrated VAR framework I show that the traditional money-demand relation, determined by a transaction effect and the opportunity cost of holding money, can no longer explain the recent development of monetary aggregates in Denmark. Instead, I argue that the introduction of housing wealth and the role of precautionary demand for liquidity improves both the explanatory power of money demand and stability of the long-run estimates. Identification of the long-run structure still suggests homogeneity between money and GDP together with a positive effect from the opportunity cost. Housing wealth enters the money-demand equation positively which is consistent with previous findings for the euro area and the US. To verify the implications of negative interest rates, I perform several forward-recursive tests and rolling-window estimations. In general, these tests confirm that the estimated moneydemand relation behaves stably over time, reflecting that the negative interest rate environment has not contributed to any permanent effect on the determination of money demand. Instead, the analysis suggests that the introduction of negative policy rates has presumably provoked a temporary shock to the coefficient on the opportunity cost.
Keywords: C32; D15; D81; E40; E41; E50; 330; Money demand; The cointegrated VAR model; Housing wealth; Long-run stability; Negative interest rates; Precautionary motive